Palynostratigraphic study of Lower Karoo rocks in the Moatize-Minjova coal basin, Mozambique - preliminary results - Lopes, Gilda (2014)
The Karoo Supergroup (KSG) is one of the most important geological units of Southern Africa. The KSG is well represented in the Tete Province along the Zambezi River in several horst and graben basins.